Sudden cardiac death after modified electroconvulsive therapy - WANG, Zhihui (Shanghai Arch Psychiatry, 2015)
Sudden deaths associated with the use of electroconvulsive therapy are rare. In this case report a 58-year-old male with a 20-year history of bipolar disorder and no history or signs of cardiac illness died from cardiac arrest within one hour of receiving an initial session of modified electroconvulsive therapy (MECT) to treat a recurrent episode of non-psychotic mania. The patient regained consciousness and was medically stable immediately after the MECT session (which did not produce a convulsion) but deteriorated rapidly after transfer to the recovery room. It was not possible to conduct an autopsy, but the authors surmise that the most probable cause was that the use of haloperidol 17 hours prior to MECT exacerbated the cardiac effects of nonconvulsive MECT. The case highlights the need for a thorough cardiac work-up on patients being considered for MECT (possibly including assessment of cardiac enzymes in older individuals) and careful consideration of the concurrent use of antipsychotic medications and MECT.